2019
DOI: 10.1002/bjs.11100
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of negative pressure wound therapy of closed groin incisions in arterial surgery

Abstract: Background: Surgical-site infection (SSI) after groin incisions for arterial surgery is common and may lead to amputation or death. Incisional negative pressure wound therapy (NPWT) dressings have been suggested to reduce SSIs. The aim of this systematic review with meta-analysis was to assess the effects of incisional NPWT on the incidence of SSI in closed groin incisions after arterial surgery.Methods: A study protocol for this systematic review of RCTs was published in Prospero (CRD42018090298) a priori, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 36 publications
5
37
0
Order By: Relevance
“…Despite the discrepancies, the Svensson-Bj€ ork meta-analysis indicated that use of incision negative pressure wound therapy after groin incision in vascular surgery reduced the incidence of SSI compared to traditional postoperative dressings. 20 This finding is similar to our own.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Despite the discrepancies, the Svensson-Bj€ ork meta-analysis indicated that use of incision negative pressure wound therapy after groin incision in vascular surgery reduced the incidence of SSI compared to traditional postoperative dressings. 20 This finding is similar to our own.…”
Section: Discussionsupporting
confidence: 92%
“…11 While assessing the original raw data of the Gombert study, the high risk of bias as reported by Svensson-Björk et al. 20 could not be confirmed. Despite the discrepancies, the Svensson-Björk meta-analysis indicated that use of incision negative pressure wound therapy after groin incision in vascular surgery reduced the incidence of SSI compared to traditional postoperative dressings.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We chose to use iNPWT for the management of these two challenging cases of degloving injuries. Several meta-analyses have shown efficacy in the prevention of wound dehiscence in high-risk cases [24][25][26][27][28][29][30][31][32][33] . We decided that the benefit obtained with use of iNPWT exceeded the cost of treatment, considering the cost of social welfare that would be incurred if these elderly patients were unable to walk.…”
Section: Discussionmentioning
confidence: 99%